Serum Exoglycosidases in Children and Adolescents With Harmful Alcohol Use. Issue 4 (July 2018) - Waszkiewicz, Napoleon; Olański, Witold; Chojnowska, Sylwia; Kołakowska, Urszula; Plewa, Katarzyna; Mielech, Włodzimierz; Bagniuk-Plewa, Anna; Wasilewska, Anna; Szulc, Agata; Szajda, Sławomir Dariusz; Zwierz, Krzysztof
Abstract : Objective: There is a lack of accurate alcohol-use biomarkers in children/adolescents due to a short drinking duration/rapid normalization of elevated markers. We checked if lysosomal exoglycosidases, elevated earlier in binge-drinking young adults, can be applicable in children/adolescents as markers of harmful alcohol use. Methods: The serum activities (pKat/mL) of α-fucosidase (FUC), β-galactosidase (GAL), β-glucuronidase (GLU), β-hexosaminidase (HEX; its HEX A and HEX B isoenzymes), and α-mannosidase (MAN) were determined in 20 healthy controls (C) and 25 children/adolescents with harmful alcohol use (intoxicated by alcohol at hospital admission –AI1 and on the next day –AI2). Results: The serum HEX A and alanine aminotransferase (ALT) activity was significantly higher in the AI1 group than in the control. The activities of FUC, GAL, GLU, HEX B, and MAN were lower in the AI group. We found fair and poor accuracy, respectively, for increased enzymes HEX A and ALT. We found fair accuracy for decreased HEX B (AI1) and MAN (AI1), good accuracy for GLU (AI2), FUC (AI2), GAL (AI1, AI2), MAN (AI2), and excellent for FUC (AI1). Correlations were found: ALT with C-reactive protein (CRP), HEX A with white blood cell (WBC) count, blood alcohol concentration with FUC, MAN and HEX B, and WBC with FUC. Conclusions: Decreased FUC, GLU, GAL, MAN values, and especially FUC (AI1) have the potential to be markers of harmful alcohol use in children/adolescents. The raised activity of HEX A and ALT points to the need for further research to check another inflammatory agent as potential alcohol marker in children and adolescents. Samples need to be collected before intravenous fluid therapy.